PENDAPATAN KELUARGA DAN PENGETAHUAN IBU TENTANG GIZI DIMASA PANDEMI COVID-19 DI PUSKESMAS SUNGAI TABUK 1 KABUPATEN BANJAR - Evy Noorhasanah; Nor Isna Tauhidah (Jurnal Terapung : Ilmu - Ilmu Sosial, 2022)
Nutritional problems can occur in various groups, especially at a very vulnerable age, namely the infancy and toddler period because of the high nutritional needs to support growth and development at this time. The current condition of the Covid-19 pandemic can affect these nutritional problems due to the increasingly difficult economic conditions of the community, such as a decrease in family income which has an impact on the ability to meet daily family needs, so that it has the potential to cause various problems, especially nutrition and health problems. In addition, the mother's knowledge of proper nutrition presentation patterns can also affect the condition of the family's nutritional status, especially during this pandemic. The consequences of nutritional problems in this pandemic era will cause short-term and long-term problems in the health, social and economic sectors. This study aims to determine the description of family income and mother's knowledge about food serving patterns during the Covid 19 pandemic. This type of research uses a description with a frequency distribution table, the population is 367 families with toddlers using accidental sampling technique. The results of this study indicate that most of the family's income is still below the minimum wage and knowledge of mothers about food serving patterns is still lacking. Suggestions to the relevant agencies need to increase community empowerment for small businesses to increase family income and increase counseling efforts on the presentation of family nutrition and provide training on processing nutritious food without requiring a lot of money.Keywords: Family income, Mother's knowledge about nutrition, Covid 19 Pandemic